1998
DOI: 10.1016/s0550-3213(98)00242-9
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of U-duality in matrix theory

Abstract: We explore various aspects of implementing the full M-theory U-duality group E d+1 , and thus Lorentz invariance, in the finite N matrix theory (DLCQ of M-theory) describing toroidal IIA-compactifications on dtori: (1) We generalize the analysis of Elitzur et al. (hep-th/9707217) from E d to E d+1 and identify the highest weight states unifying the momentum and flux E d -multiplets into one E d+1 -orbit. (2) We identify the new symmetries, in particular the Weyl group symmetry associated to the (d + 1)'th node… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
164
0
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(171 citation statements)
references
References 49 publications
3
164
0
4
Order By: Relevance
“…These stringy symmetries lead to new extended states, which were discovered and classified in Refs. [3][4][5]. These were revisited recently in Ref.…”
Section: Preliminaries On Dualities and Branesmentioning
confidence: 98%
See 2 more Smart Citations
“…These stringy symmetries lead to new extended states, which were discovered and classified in Refs. [3][4][5]. These were revisited recently in Ref.…”
Section: Preliminaries On Dualities and Branesmentioning
confidence: 98%
“…Moreover, it was soon realized that the interplay between dualities and branes leads to a whole new family of extended objects, with Dp, NS5 and KKM being just a fraction of it [3][4][5][6]. These new BPS-objects have codimension 2 and are obtained as orbits of the U-duality group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fields C (2n−1) denote the R-R (2n − 1)-form potentials, B the Kalb-Ramond field and B its Hodge dual, the NS-NS 6-form potential. The field N (7) is the field that couples to the Type IIA Kaluza-Klein monopole, and N (8) to the so-called (6, 1 2 ; 3)-brane 3 , an "exotic" brane (not predicted by the Type IIA spacetime supersymmetry algebra), first mentioned in [14,15,16]. The currents I give the couplings between the Matrix (string) theory and the linearised background fields [11,12,13] and are functions of the matrix valued transverse coordinates X i , the world volume scalar A and their derivatives 4 .…”
Section: The Action For Multiple Type Iia Gravitational Wavesmentioning
confidence: 99%
“…The Uduality [1], which makes non-trivial connections among consistent superstring theories, relates various branes in each theory. It was shown that M-theory compactified on T d has the U-duality symmetry group E d(d) (R) in lower dimensions [2][3][4]. BPS branes in superstring theories form lower-dimensional multiplets under the U-duality group.…”
Section: Introductionmentioning
confidence: 99%